2020
DOI: 10.1038/s41598-020-63502-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term high-temperatures on the growth, development and reproduction in the fruit fly, Bactrocera tau (Diptera: Tephritidae)

Abstract: Bactrocera tau (Walker) (Diptera: Tephritidae) is an economically important invasive pest, that is capable of seriously reducing the quality and yield of vegetables and fruits, it was first recorded from Fujian province in 1849 and later introduced to Yunnan province in 1912 as a result in trade fruits and vegetables of China. In recent years, with the onset of global climate change and the accompanying increase in the greenhouse effect, elevated climatic temperatures have become one of the main environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
0
15
1
Order By: Relevance
“…13 However, once the temperature exceeds their tolerance limits, it will lead to short (e.g., decreased survival rate or immediate death) and long-term adverse effects (i.e., potential carry-over effects on subsequent development stages and fecundity). [14][15][16][17] Most insect species suffer from temperature fluctuations in their dwelling environment throughout their ontogeny, which affects physiological processes and ecological functions. It is known that different developmental stages of insects have different thermal sensitivities, so high temperatures experienced in early ontogeny can affect biological characteristics and heat tolerance capacities in later development stages or the next generation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 However, once the temperature exceeds their tolerance limits, it will lead to short (e.g., decreased survival rate or immediate death) and long-term adverse effects (i.e., potential carry-over effects on subsequent development stages and fecundity). [14][15][16][17] Most insect species suffer from temperature fluctuations in their dwelling environment throughout their ontogeny, which affects physiological processes and ecological functions. It is known that different developmental stages of insects have different thermal sensitivities, so high temperatures experienced in early ontogeny can affect biological characteristics and heat tolerance capacities in later development stages or the next generation.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 To date, more and more studies have begun to pay attention to the impact of fluctuating temperature on the performance and fitness of insects, yet most studies are carried out in different constant temperatures. 8,10,15,17,19,20,[31][32][33][34][35] Although these studies have shown that high temperatures affect the performance of insects, the experiments are based on either constant high temperatures or short-time exposures to high temperatures, and thus the studies may not adequately reflect the variable temperature conditions experienced in the natural environment. In fact, some studies have shown that using constant temperature conditions to explore the performance thermal response of insects may not reflect the thermal responses of insects under real field conditions because they do not mimic the fluctuating temperature conditions that occur within the natural environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This alteration manifested mainly as a delay in the pre-oviposition and peak period of oviposition, decreased egg production and hatching rate, gradual shortening of the life span in both males and females, and an increase in the female offspring ratio (Zhou et al, 2011;Stazione et al, 2021). Huang et al (2020) reported that short-term exposure to high temperatures of over 42°C was not suitable for the successful development of Z. tau, while the short-term application of high temperatures of over 40°C was not suitable for successful reproduction in Z. tau. However, there is a lack of further observation on the reproductive behavior in Z. tau under short-term high temperature exposure.…”
Section: Introductionmentioning
confidence: 99%